Sleep Quality of Patients with COVID-19 after Hospital Discharge: COVID-19 SLEEP QUALITY - Gundogdu, Nevhiz; Tanriverdi, Mustafa (Progress in Nutrition, 2022)
Objective: Sleep is very important for both our psychological and physical health and can be affected by many factors. We planned to evaluate the sleep quality of patients with COVID-19 in their first month follow-up and investigate whether it is related to the severity of the disease and the current symptoms and laboratory findings of the individual. Methodology: The study was designed observational cross-sectional questionary. Covid-19 diagnosed and hospitalized patients who agreed to participate in the study were included in the study on August 2020-March 2021. The patients who came to the outpatient clinic for the 1st month of inpatient treatment were included in the study. Patients with pregnant, any known sleep disorder were excluded. Covid-19 severity was defined as location of treatment in hospital: admission place intensive care unit (ICU) was accepted as severe case; the ward was accepted as mild cases. A questionnaire including demographics’ (age, gender, body mass index), co-morbidities, current complaints and the Pitsburg sleep quality test was filled in at the time of admission to the outpatient clinic. All patients grouped according to PSC as good sleep group (PSC<5) and bad sleep group(PSC>=5). Study groups and patients at hospital and after 1s m discharge PSC scores were compared according to recorded data. t Results: In study period 83 patients (49 male and 34 female)had full-fill criteria and admitted in to the study. Those patients were treated %30.1 in ICU and %69.9 in the ward. The sleep score value for the 1st month ranged from 0 to 20 median 5. The sleep duration (hour) value ranged from 3 to 11, with an average of 7.2±1.5. 56.6% (n=47) of the patients had poor sleep quality according to the Pitsburg scale. Conclusions: The sleep quality of covid-19 patients was impaired in the 1st month controls and was not associated with the severity of the covid-19 disease